Distributed Learning in the Classroom: Effects of Rereading Schedules Depend on Time of Test - Greving, Carla E.; Richter, Tobias (Frontiers in Psychology, 2019)
Research with adults in laboratory settings have shown that distributed rereading is a beneficial learning strategy, but its effects depend on time of test. Measured immediately after rereading yields no benefits or even detrimental effects on learning, but the beneficial effects emerge two days later. In a preregistered experiment, the effects of distributed rereading were investigated in a classroom setting with school students. Seventh-graders (N = 191) reread a text either immediately or after one week. Learning outcomes were measured after 4 minutes or 1 week. Participants in the distributed rereading condition reread the text more slowly, perceived reading as more difficult, predicted lower learning success, and reported lower on-task focus. At the shorter retention interval, massed rereading outperformed distributed rereading. Contrary to students in the massed condition, students in the distributed condition showed no forgetting from the short to long retention interval. As a result, they performed equally well to the students in the massed condition at the longer retention interval. Our results show that distributed rereading is perceived as a difficulty, leading to higher effort during rereading. Its effects on learning indeed depend on time of test, but no beneficial effects were found, not even in the long run.